Analisis Pengaruh ROA, ROE, dan NPM Terhadap Return Saham (Literature Review Manajemen Keuangan Perusahaan) - Davidson Juniardy Hadu, Charles; A. Manafe, Henny; Paulina Bibiana, Rere (Jurnal Ilmu Multidisiplin, 2023)
Previous research or relevant research is very useful for research and literature review of scientific work. This article reviews the impact of ROA, ROE, and NPM in a literature review on stock returns on corporate financial management. This article aims to develop a hypothesis about the effect of the variables to be used in future studies. The findings of this research are: 1) Return on assets (ROA) has a positive and important impact on stock returns; 2) Return on equity (ROE) has a positive and important impact on stock returns; 3) Net profit margin (NPM) has a positive and important impact on stock returns; 4) ROA, ROE, and NPM have a positive and important impact on stock returns together.